Data collection algorithm for mobile sink in delay-constrained network - Xian-ling LU; Ying-ying WANG (Tongxin xuebao)
In real-time applications,the delay constraint limits the speed and the trajectory of mobile sink which in consequence restrains the communication time between the sensor nodes and the sink.So it is difficult to balance delay requirement with the data collecting efficiency.To address the problem above,an efficient data collection algorithm MSDC for sensor networks is proposed.It finds an optimal sink trajectory in the data buffering and uses the mobility of sink to improve the data collection performance in the limited time.The simulation results show that the algorithm can improve the network data collection capacity throughput,reduce the energy consumption and prolong the network lifetime.